Social Determinants and Access to Induced Abortion in Burkina Faso: From Two Case Studies - Ramatou Ouédraogo; Johanne Sundby (Obstetrics and Gynecology International)
Unsafe abortion constitutes a major public health problem in Burkina Faso and concerns mainly young women. The legal restriction and social stigma make abortions most often clandestine and risky for women who decide to terminate a pregnancy. However, the exposure to the risk of unsafe induced abortion is not the same for all the women who faced unwanted pregnancy and decide to have an abortion. Drawn from a qualitative study on the issue of abortion in Ouagadougou, Burkina Faso’s capital, the contrasting cases of two young women who had abortion allow us to show how the women’s personal resources (such as the school level, financial resources, the compliance to social norms, the social network, etc.) may determine the degree of vulnerability of women, the delay to have an abortion, the type of care they are likely to benefit from, and the cost they have to face. This study concludes that the poorest always pay more (cost and consequences), take longer to have an abortion, and have more exposure to the risk of unsafe abortion.